2012
DOI: 10.5187/jast.2012.54.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Dielectric Barrier Discharge Plasma System for Inactivating Pathogens on Cheese Slices

Abstract: The objective of this study was to evaluate the potential use of a dielectric barrier discharge (DBD) plasma system to improve microbial safety of sliced cheese. The atmospheric pressure plasma (APP) effect on visual appearance and a sensory evaluation were also carried out. The number of Escherichia coli inoculated on cheese slices decreased by 0.09, 0.47, 1.16 and 1.47 log cycles with helium (4 liters/min [lpm]) and 0.05, 0.87, 1.89 and 1.98 log cycles with He/O2 mixture (4 lpm/15 standard cubic centimeters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…O 3 ) and others (Kostov et al, 2010) and L. innocua possesses a similar or even higher resistance to ozone exposure compared to L. monocytogenes (Vaz-Velho et al, 2001), L. innocua was selected as an appropriate non-pathogenic representative for the pathogen in the following experiments. Figure 3(a) indicated that the DBD treatment was more effective against E. coli, consistent with previous studies suggesting that DBD was an effective technique to inactivate both Gram-positive and Gramnegative bacteria, with Gram-negative bacterium (E. coli) eliminated more rapidly (Lee et al, 2012;Sun et al, 2007). Furthermore, the images obtained with atomic force microscopy revealed that the treated E. coli cells exhibited aggregate or even collapse morphologies whereas L. innocua suffered only a little structural erosion without visible morphological damages ( Figure S2).…”
Section: Germicidal Effect: the Type Of Microorganismsupporting
confidence: 88%
See 2 more Smart Citations
“…O 3 ) and others (Kostov et al, 2010) and L. innocua possesses a similar or even higher resistance to ozone exposure compared to L. monocytogenes (Vaz-Velho et al, 2001), L. innocua was selected as an appropriate non-pathogenic representative for the pathogen in the following experiments. Figure 3(a) indicated that the DBD treatment was more effective against E. coli, consistent with previous studies suggesting that DBD was an effective technique to inactivate both Gram-positive and Gramnegative bacteria, with Gram-negative bacterium (E. coli) eliminated more rapidly (Lee et al, 2012;Sun et al, 2007). Furthermore, the images obtained with atomic force microscopy revealed that the treated E. coli cells exhibited aggregate or even collapse morphologies whereas L. innocua suffered only a little structural erosion without visible morphological damages ( Figure S2).…”
Section: Germicidal Effect: the Type Of Microorganismsupporting
confidence: 88%
“…Thus, under these plasma-treatment conditions, the color quality of the sliced cheeses was evidently not affected (Table 1). Kim et al (2011) and Lee et al (2012) investigated the effect of He/O 2 APP, powered by a 13.56 MHz and 50 kHz supply, on surface color of bacon and cheese, respectively, and found that the plasma-treated bacon and cheese became redder (higher a*), yellower Food Science and Technology International 26(8) (higher b*), and dimmer (lower L*) at higher input power or with longer plasma exposure. An increase in the yellow index (b*) might be due to plasma-mediated oxidation, which was caused by greater oxidativedamage effect proportional to plasma-exposure time (Lee et al, 2012).…”
Section: Surface Color Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Gramnegative bacteria such as E. coli O157:H7 possess a unique outer membrane in their cell envelope and could be more vulnerable than Gram-positive bacteria such as B. cereus and B. subtilis, which have a thick peptidoglycan structure on the outside of the cell that is resistant to chemical changes. Lee et al (2012) reported that the outer membrane of Gram-negative bacteria exhibited structural damage following exposure to cold plasma, whereas Gram-positive bacteria did not show the same degree of morphological changes.…”
Section: Microbial Analysesmentioning
confidence: 96%
“…Enteritidis and B. cereus spores. On the other hand, it seems to exist an agreement, although with some exceptions (Reineke et al, 2015), in that the addition of small amounts of oxygen to noble gases, such as helium (Gweon et al, 2009; Kim et al, 2011, 2013; Lee et al, 2011, 2012a; Galvin et al, 2013) and argon (Surowsky et al, 2014), or nitrogen (Lee et al, 2011, 2012b) improves the antimicrobial effectiveness of NTAP against vegetative cells and spore-forming bacteria (Table 1). This effect is mainly attributed to a higher formation of reactive oxygen species, such as hydroxyl and hydroperoxyl radicals, atomic oxygen, hydrogen peroxide, singlet oxygen and ozone, all of them with a high antibacterial activity.…”
Section: Factors Determining the Antimicrobial Effectiveness Of Ntapmentioning
confidence: 98%